2017
DOI: 10.1016/j.pep.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of the fission yeast Ndc80 complex

Abstract: The Ndc80 complex is a conserved outer kinetochore protein complex consisting of Ndc80 (Hec1), Nuf2, Spc24 and Spc25. This complex comprises a major, if not the sole, platform with which the plus ends of the spindle microtubules directly interact. In fission yeast, several studies indicate that multiple microtubule-associated proteins including the Dis1/chTOG microtubule polymerase and the Mal3/EB1 microtubule plus-end tracking protein directly or indirectly bind Ndc80, thereby ensuring stable kinetochore-micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The mitotic regulator NDC80 is highly expressed in various human malignancies, including hepatocellular carcinoma, colon cancer and osteosarcoma (33)(34)(35). NDC80 is also called Hec1, and its complexes together with NUF2 component of NDC80 kinetochore complex (NUF2), SPC24 component of NDC80 kinetochore complex (SPC24) and SPC25 component of NDC80 kinetochore complex (SPC25) participate in the spindle assembly checkpoint and regulation of mitosis and chromosome segregation (36)(37)(38)(39). Lin et al showed that Hec1 sequentially recruits Zwint-1 and ZW10 to kinetochores during the mitotic phase of the cell cycle, and interruption of the centromeric recruitment led to chromosomal missegregation, incomplete activation of spindle examination points, and ultimately cell death (31).…”
Section: Discussionmentioning
confidence: 99%
“…The mitotic regulator NDC80 is highly expressed in various human malignancies, including hepatocellular carcinoma, colon cancer and osteosarcoma (33)(34)(35). NDC80 is also called Hec1, and its complexes together with NUF2 component of NDC80 kinetochore complex (NUF2), SPC24 component of NDC80 kinetochore complex (SPC24) and SPC25 component of NDC80 kinetochore complex (SPC25) participate in the spindle assembly checkpoint and regulation of mitosis and chromosome segregation (36)(37)(38)(39). Lin et al showed that Hec1 sequentially recruits Zwint-1 and ZW10 to kinetochores during the mitotic phase of the cell cycle, and interruption of the centromeric recruitment led to chromosomal missegregation, incomplete activation of spindle examination points, and ultimately cell death (31).…”
Section: Discussionmentioning
confidence: 99%
“…As shown diagrammatically in Figure 3A, plasmid-borne expression of asp1 1-364 increases intracellular IP 8 , while asp1 365-920 expression reduces (but does not eliminate) IP 8 levels [36]. S. pombe kinetochores complexes consist of the same core modules found in human and S. cerevisiae such as KMN(human)/NMS( S. pombe ) and CCAN(human)/Ctf19( S. cerevisiae )/Mis6-Mal2-Sim4( S. pombe ) [84-88]. Expression of either asp1 1-364 or asp1 365-920 from a plasmid had no or only a moderate effect on the growth of 4 temperature sensitive S. pombe KMN mutant strains tested (Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical assays and transmission electron microscopy analysis of the NDC80 complex has shown a conserved ‘head‐rod‐head’ architecture in Saccharomyces cerevisiae and humans (Ciferri et al ., 2005; Wei et al ., 2005, 2006). In Schizosaccharomyces pombe , the NDC80 complex may co‐precipitate with polymerized MTs, and this binding is sensitive to ionic strength (Matsuo et al ., 2017; Powers et al ., 2009). In humans, the C‐termini of SPC24 and SPC25 anchor the NDC80 complex to the kinetochore protein, while the N‐terminal domains of NUF2 and HEC1/NDC80 bind to the positive ends of spindle MTs (DeLuca et al ., 2006; Sundin et al ., 2011; Wan et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%